The Poetics of the Orphan in Abdelkébir Khatibi's Early Work - Matt Reeck (Journal of French and Francophone Philosophy, 2017)
Like many North African, Francophone, and world writers whose lives span the historic divide of independence from colonialism, Abdelkébir Khatibi’s work focuses in large part upon the idea of encounter, or, in French, “rencontre.” In this paper I focus upon the figure of the orphan in La mémoire tatouée and Le lutteur de classe à la manière taoïste, two of his earliest texts. By focusing upon the orphan as a multivalent term, and by following Khatibi’s emphasis upon language, literature, and even life itself as a game or experiment, we can see how Khatibi creates an ethics of encounter that derives its meaning from recuperating a negatively connotated word and transforming it into a term of positive value. With the term “orphan,” he shows how through encountering the Other, by extending beyond into the unknown, by exceeding the circumscriptions of ancestry, identity, and national culture, the individual rises into a new status of free living. Moreover, it is equally through the practice of writing that life redounds with life; writing for Khatibi is never a mimetic representation of life per se but a space for experimenting, for discovery, and for exceeding the parochial nature of an individual’s physical placement in the world. In this sense, the orphan status of his writing shows itself through his aggressively restless, polyphonic, and ageneric writing that uses the localization of genre only as a hinge to push against in the quest to articulate a new relation to the world.